(3cGTaI GdZeI Yf GdGYJQGV Ydi GdCFeIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ HhLhO GdCFeI SdWGf GdESdGe s
(3BNQgG (B:s
(3hLeY Ted GdeSdejf , hbWY OGHQ GdedGMOI GdeaSOjf , hGdfjI ai Pdc UGObI (B,(3MSfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cJHJ HYV GdYfGhjjf HGdMeQIs
(3Ydi MhGTgjG HYV GdJYdjbGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B10) s
Keywords: (3abg GdePGgH GdCNQis